EVIDENCE-BASED RECRUITING : HOW TO BUILD A COMPANY OF STAR PERFORMERS THROUGH SYSTEMATIC AND REPEATABLE HIRING PRACTICES - Tarki, Atta (New York : McGraw-Hill Education, 2020)
"A renowned executive recruitment expert provides you with a playbook to implement systematic, repeatable, best-in-class hiring practices to give your business maximum competitive advantage. Data and analytics are reshaping countless industries as they turn from anecdotal to evidence-based practices. Yet while most aspects of business operations today rely on clearly defined measures of success that are continuously tracked and improved, in most organizations, hiring and recruitment is still run on intuition. Evidence-Based Recruiting flips that script, putting the power of big data and analytics to work for you. Written by the respected CEO of a pre-eminent specialized executive search firm, this book makes a case for best-in-class recruiting methods, showing how companies like Google and Netflix utilize evidence-based techniques to land top-tier talent, and how you can do the same by implementing systematic and repeatable processes that lead to better and more consistent hiring outcomes. You will be given the elements of an evidence-based approach, learn how to distinguish good evidence from bad, and understand why many hiring predictions fail-and what you can do about it. A must-read for CEOs, hiring managers, and human resources professionals, Evidence-Based Recruiting provides you with the tools you need to thrive in the new era of talent acquisition"-- Provided by publisher.
Includes index
Keywords: Executives -- Recruiting; Employee selection; Employee selection; Executives -- Recruiting